PENGEMBANGAN APLIKASI BANK SAMPAH DENGAN METODE EXTREME PROGRAMMING - Luluk Suryani; Ery Murniyasih; Marcelinus Petrus Saptono; Raditya Faisal Waliulu; Imam Trianggoro Saputro; Sonny Rumalutur (LPPM Poltek ST Paul, 2022)
In the era of technology 5.0, many people have been able to create new value through technological developments that occur from time to time. This change can help minimize the gap in people and economic problems in the future. One of the fastest growing technologies every year is an application on a smartphone. There are so many variations of applications, this is because smartphone users are increasing from time to time. Existing developments are an opportunity for the Garbage Bank to support the zero waste program and improve Garbage Bank services to the community. This study aims to develop a Garbage Bank application as a means of ordering waste transportation services and viewing educational information, as well as activities from the Sorong Raya Garbage Bank (BSSR). Application development will use the Extreme Programming method, with the stages of Planning, Design, Coding, and Testing. This method was chosen because it can increase user satisfaction due to continuous communication in application development and is suitable for use by small teams. The application can be used on the Android operating system. The application was developed using Android Studio and Flutter tools. To ensure the system is running properly, it will be tested with alpha testing. The results of the alpha testing of all functional systems can run as expected so it can be concluded that the application is feasible to use.